The Process of Providing Spiritual Care to Muslim Cancer Patients - Alireza Irajpour; Maryam Moghimian (Journal of Muslim Mental Health)
Spiritual care is a component of the holistic approach to care and treatment. Also, health care providers face many challenges when it comes to spiritual care. To address these challenges, the implementation process must be identified and possible outcomes examined. This study aimed to investigate the process of providing spiritual care to Muslim cancer patients. This descriptive qualitative-exploratory research was conducted in 2020, in which 27 participants were selected through purposive sampling and had semi-structured interviews. The data analysis revealed two themes and five sub-themes including the process of spiritual care (identifying spiritual needs, analyzing situations to meet spiritual needs, expanding spiritual care and spiritual promotion) and the outcome of spiritual care (spiritual promotion and some erosion of faith and spiritual belief). In this study, the received topics have been related to spiritual care which can help improve patient care. The findings of this study can shed light on the process and outcome of spiritual care for health care providers, and can be utilized in the design of a spiritual care program for these patients.